2000
DOI: 10.1097/00001622-200011000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Lung resistance-related protein/major vault protein and vaults in multidrug-resistant cancer

Abstract: Tumor cells that are insensitive to anticancer drugs frequently have a multidrug-resistant (MDR) phenotype. Proteins that can be involved in this phenomenon are transport-associated proteins such as P-glycoprotein, multidrug-resistance protein 1, breast cancer resistance protein, and lung resistance-related protein (LRP). LRP was identified as the major vault protein (MVP), the main component of multimeric vault particles. With the recent identification of the two minor vault proteins as telomerase-associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
119
1
8

Year Published

2001
2001
2011
2011

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 159 publications
(130 citation statements)
references
References 59 publications
2
119
1
8
Order By: Relevance
“…Increased levels of MVP expression have been linked to multidrug resistance (MDR) (Scheffer et al, 2000) and can be of clinical value in predicting the response of tumors to chemotherapy (Hofer and Hermann, 2001). Our studies indicate that MVP is selectively expressed compared to astrocytes and at higher frequency in glioblastomas compared to low-grade astrocytomas.…”
Section: Major Vault Proteinmentioning
confidence: 99%
“…Increased levels of MVP expression have been linked to multidrug resistance (MDR) (Scheffer et al, 2000) and can be of clinical value in predicting the response of tumors to chemotherapy (Hofer and Hermann, 2001). Our studies indicate that MVP is selectively expressed compared to astrocytes and at higher frequency in glioblastomas compared to low-grade astrocytomas.…”
Section: Major Vault Proteinmentioning
confidence: 99%
“…Although the exact function of vaults is not yet known, in humans, the elevated vault levels have been used to predict whether tumors will acquire multidrug resistance (reviewed in Ref. 4). They have a mass of 13 MDa, and their three-dimensional reconstruction to 22-Å resolution indicated that the inside of the barrel is spacious enough to encompass an intact ribosome, consistent with a carrier/sequestration capacity (5,6).…”
mentioning
confidence: 99%
“…The precise cellular function(s) of the vault complex are not yet completely clear (for reviews see Refs. [1][2][3].…”
mentioning
confidence: 99%